Prototype Design Of User Centered Design Based On Ucd (User Centered Design) For Handiser Services at Pt Semen Indonesia Distributor - Ambami, Sinta Aisyah; Safitri, Anita (Journal of Digital Business and Innovation Management, 2025)
Advances in information technology, especially in digital-based services, have created potential business opportunities, including in the provision of handyman services that are easily accessible to the public. This has encouraged PT Semen Indonesia Distributor to develop a new business in the provision of handyman services. To facilitate public access and interaction, a website is needed that functions as a portal for information services for handyman services. Therefore, this prototype is designed to help users choose the right handyman services and provide information related to services, prices, and locations of handymen. The User Centered Design UCD method is used to ensure that the website design is in accordance with user needs and convenience, and provides more efficient interactions. This study uses a research and development (R&D) approach with a technology readiness level (TKT) of 6. Data collection was carried out through observation and interviews with five respondents from the information communication technology and digital marketing divisions of PT SID. Based on the results of the needs analysis, the prototype was developed using the Figma tool, starting from making wireframes to high fidelity prototypes. The evaluation was carried out using the Black Box Testing method to test the functionality on the main pages such as Home, Our services, products, profiles, articles, and choose us, and the results showed that all features had run according to the specified specifications and according to user expectations.